Cognitive strategies of law students in writing opinion text - Prihatini, Arti; Asrini, Hari Windu; Wuryaningrum, Rusdhianti; Inayati, Nina (Intelektual Pustaka Media Utama, 2025)
Writing skills are one of the determining factors for law students' success, but it is their biggest problem. This problem stems from the lack of grammar mastery and learning barriers during the COVID-19 pandemic. Therefore, this study aims to describe cognitive strategies for law students in writing opinion texts during the COVID-19 pandemic and the pedagogical implications. This study employed a mixed method. The research participants were 200 first-year students of the 2021-2022 academic year. Data collection methods are inventory and open-ended questions. The research found that students with Indonesian as first language (L1) are high in cognitive strategies, while second language (L2) students are moderate. The highest cognitive strategy is to look for reference sources on grammar rules on the internet. The correlation found a significant relationship among cognitive strategy. The most significant is the relationship between all cognitive strategies and developing explicit knowledge of grammar. Our findings provide pedagogical implication that writing instruction needs to use cognitive strategies as grammar learning strategies within a contextual-communicative approach in law. In conclusion, cognitive strategies can be used integratively in writing by emphasizing the use of explicit language knowledge and various digital sources for L1 and L2 learners.